Inisiatif Komunitas dan Jaringan Lokal Petani Kopi Gunung Kamojang: Studi Binaan PT PLN Indonesia Power Kamojang POMU - Sheliana Nugraha Muslim; Eva Wirabuana; Dito Hastha Krisandy; Ahsani Paramitasari; Rifky Taufiq Fardian (Publikasi Indonesia, 2022)
Over the past decades, coffee farmers in Kamojang have faced the same problems as farmers around the world. This ethnographic research among the coffee farming community of Wanaka Kopi Gunung Kamojang Farmers Group is located in Kamojang, Laksana Village, Ibun District, Bandung Regency, West Java from 2019-2022. This research documents local initiatives to address problems through the establishment of a network of Wanaka Kopi farmers in the Gunung Kamojang Farmer's Group, revitalization of traditional production patterns, local integration into the national coffee commodity chain and entrepreneurship of coffee-derived product innovation. Conceptualizing how to empower local coffee farmers, the Wanaka Kopi Gunung Kamojang Farmer Group generates and implements the initiative, this journal suggests that by leveraging their social network, local farmers revive their economic output. There is a decent collective bargaining position in the realm of the coffee commodity chain system, giving them the opportunity to survive the deregulation of forestry investment, which is a problem for farmers and is undeniably affected by climate change.